Soft computing approach for solving elevator scheduling problem - Norzatul Hajar, Abd Majid (Universiti Malaysia Sarawak, UNIMAS, 2010)
Elevator scheduling problem involves finding an optimal path of certain number of elevators movement in a building with certain number of floors. It is formulated as an integer programming problem. In order to solve the scheduling problem on elevator, a genetic algorithm as part of soft computing is used in a real time system. It becomes an option because the minimum optimization can be counter through this method where some specific criteria have to be fulfilled that will result in the minimization of passengers travelling and waiting time in or for an elevator. In order to manipulate the scheduling problem solution, designed and developed simulation software for the optimization of elevator scheduling problem is introduced and presented by using soft computing methodology.